Undermining Colonial Space In Cinematic Discourse - Dr. Ammar Ibrahim Mohammed Al-Yasri (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is no doubt that artistic races are the fertile factor in philosophy in all of its perceptions, so cinematic discourse witnessed from its early beginnings a relationship to philosophical thought in all of its proposals, and post-colonial philosophy used cinematic discourse as a weapon that undermined (colonial) discourse, for example cinema (Novo) ) And black cinema, Therefore, the title of the research came from the above introduction under the title (undermining the colonial space in cinematic discourse) and from it the researcher put the problem of his research tagged (What are the methods for undermining the colonial space in cinematic discourse?) And also the first chapter included the research goal and its importance and limitations, while the second chapter witnessed the theoretical framework It included two topics, the first was under the title (post-colonialism .. the conflict of the center and the margin) and the second was under the title (post-colonialism between cinematic types and aspects of the visual form) and the chapter concludes with a set of indicators, while the third chapter included research procedures, methodology, society, sample and analysis of samples, While the fourth chapter included the results and conclusions, and from the results obtained, the research sample witnessed the use of undermining the (colonial) act, which was embodied in the face of violence with violence and violence with culture, to end the research with the sources.